Evaluation of KGB heritage: why and what for it is important - Ragauskas , Petras (Genocidas ir rezistencija, 2006)
The topic of evaluating the legacy of the KGB is quite broad, but the most important issue for the public is the issue of evaluation of secret cooperation and secret collaborators. The most appropriate evaluation of the KGB legacy for the state and society is one that satisfies, as far as possible, the following interests (with as little as possible damage to the others): the interest to know, the interest to live safely, the interest to justice, and the interest to restore social peace. Since the content of these interests is not unambiguous, an additional criterion must be selected: it must be decided whether the focus is to be on the present or on the future. From the future perspective, many things look differently. Both justice and social peace are more in line with open speaking up. If this is done ten years from now, questions about justice will pile up and dreams of social peace will move further into the future. One can only feel secure when all the mysteries of the KGB legacy have been resolved.
Keywords: KGB; lustration; agents; desovietisation